An Autonomous Health Monitoring and Fall Detection Using Wban - M.Sheriff, Mr.; R.Deepika, G.; Sandhiya, S.; Sowmiya, S. (International Journal of Engineering and Technology, 2018)
Abstractâ€”Over the last couple of decades, the walkable patients who are all using the wired sensors are bedbound and also they suffer from psychological stress. In order to overcome this inconvenience, our project made this as wireless. This is based up on the communication devices like mobile phones and WBAN for the real time analysis of the patient health [1].We have two section, one is transmitter and another one is receiver. In transmitter side, the basic essential sensors like temperature sensor, BP sensor, heartbeat sensor,SPO2 sensor(measures glucose level), MEMS sensor(detects the fall) and GPS module are connected to Node MCU(Microcontroller Unit).In receiver side all the sensors and the GPS module are connected to cloud storage through node MCU. The status about the patientâ€™s health will be continuously updated on the cloud storageand in the case of abnormal values, the location of the patients will be send as a mail to the medical practioners and concern person.Â